Spiral arms in the protoplanetary disc HD100453 detected with ALMA: evidence for binary-disc interaction and a vertical temperature gradient - Rosotti, Giovanni Pietro; Benisty, M.; Juhász, A.; Teague, R.; Clarke, C.; Dominik, C.; Dullemond, Cornelis; Klaassen, P. D.; Matrà, L.; Stolker, T. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Scattered light high-resolution imaging of the protoplanetary disc orbiting HD100453 shows two symmetric spiral arms, possibly launched by an externa
Gesehen am 21.02.2020
Advance access publication 2019 November 4